Geração experimental de speckles com estatística da intensidade weibull - Amaral, João Paulo de (2016)
Currently there are many studies that seek to produce patterns of speckles with statistics that deviates from the Rayleigh statistics, the so-called speckles non-Rayleigh. In this job we use a phase only computer-generated hologram to code both phase and amplitude of a power of Rayleigh speckles. This method allows us to generate speckles with enhanced and reduced contrast without any optimization process. We explore non-Rayleigh speckles and unveil, theoretically and experimentally, its first order statistical properties. These speckles may find applications in syntheses of disordered optical potentials for cold atoms and colloidal particles, in speckle illumination imaging, and in wave interference studied through spatial intensity correlation. Stressing that our results are grounded by a theoretical model based on a transformation of the amplitude of Rayleigh speckle field an exponeciação, maintaining the phase of the field untouched.